Utilização do jogo sério labirinto como instrumento de identificação de fragilidade em idosos - Bevilaqua, Sandrene de Oliveira (2024)
Abstract: Global aging poses significant challenges to the health and quality of life of the elderly, with frailty being a common condition associated with this process. Monitoring and assessing the evolution of frailty are crucial for implementing effective and personalized interventions. Objective: This research aimed to contribute to the use of the labyrinth game in evaluating the performance of the elderly and the early identification of frailty, characterizing the elderly regarding their frailty and comparing the performance in the game with different domains (sociodemographic, physical, and social). Materials and methods: This is a descriptive research with frailty diagnostic measures conducted in Santa Maria/RS, involving 49 elderly individuals of both genders residing in long-term care facilities for the elderly in the city and patients from the occupational therapy outpatient clinic of the university hospital in the city, selected by convenience using non-probabilistic sampling. Inclusion criteria included age, preserved gait, and understanding of two simple verbal commands, with voluntary acceptance and interest. Elderly individuals unable to respond to questionnaires, bedridden, wheelchair-bound, or with pathologies affecting walking capacity were excluded, ensuring active participation. Data collection took place from August to September 2023, only after acceptance and signing of the Informed Consent Form. Sociodemographic and clinical characterization of participants was conducted through a questionnaire developed by the researcher, consisting of 15 questions, and frailty assessment used the Brazilian version of the Tilburg Frailty Indicator – TFI. The entire evaluation process, from the questionnaire application to the labyrinth game, lasted an average of approximately 30 minutes and was conducted at the long-term care facility and the occupational therapy outpatient clinic, ensuring an appropriate environment for assessments. Results: The results showed significant differences in the physical, psychological, and social domains between frail (n=26) and non-frail (n=23) groups, as well as variations in age, marital status, polypharmacy, and the use of walking aids. The time used in the labyrinth game performance was a good predictor for distinguishing frailty categorical profiles, Frail group (p=0.001); the number of errors during game performance also differentiated between groups (Frail-Non-frail) (p=0.001). Conclusion: The differences found emphasize the comprehensive influence of frailty on the lives of the elderly, emphasizing the importance of early detection to improve quality of life. The time used in the analog labyrinth game performance and the number of errors made during its execution proved to be a promising indicator for identifying frailty in the elderly.